2018
DOI: 10.2196/jmir.9710
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Cognitive Behavioral Therapy for Symptoms of Depression and Anxiety Among Patients With a Recent Myocardial Infarction: The U-CARE Heart Randomized Controlled Trial

Abstract: BackgroundSymptoms of depression and anxiety are common after a myocardial infarction (MI). Internet-based cognitive behavioral therapy (iCBT) has shown good results in other patient groups.ObjectiveThe aim of this study was to evaluate the effectiveness of an iCBT treatment to reduce self-reported symptoms of depression and anxiety among patients with a recent MI.MethodsIn total, 3928 patients were screened for eligibility in 25 Swedish hospitals. Of these, 239 patients (33.5%, 80/239 women, mean age 60 years… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
118
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(134 citation statements)
references
References 50 publications
5
118
2
4
Order By: Relevance
“…The comparison of the mean scores of various parameters regarding the main symptoms of myocardial infarction in the studied groups before intervention was indicative of the consistency of these two groups and the comparison of the mean scores of the different parameters of the main symptoms of myocardial infarction in the subsequent study groups. The intervention in the test group has signif icantly increased while compared with the control group, which is consistent with the results of the study by Norlund (2018); reported that the behavioral and physical counseling after few months improved the patient's physical and behavioral behavior and after a year of quality of life improved the quality of patients. Also, in a study of Baghaei (2015) the implementation of this model evidenced the improvement in the quality of life of patients in the test group in all aspects of the physical, emotional and general, and the test group which differed statistically from the control group.…”
Section: Resultssupporting
confidence: 89%
“…The comparison of the mean scores of various parameters regarding the main symptoms of myocardial infarction in the studied groups before intervention was indicative of the consistency of these two groups and the comparison of the mean scores of the different parameters of the main symptoms of myocardial infarction in the subsequent study groups. The intervention in the test group has signif icantly increased while compared with the control group, which is consistent with the results of the study by Norlund (2018); reported that the behavioral and physical counseling after few months improved the patient's physical and behavioral behavior and after a year of quality of life improved the quality of patients. Also, in a study of Baghaei (2015) the implementation of this model evidenced the improvement in the quality of life of patients in the test group in all aspects of the physical, emotional and general, and the test group which differed statistically from the control group.…”
Section: Resultssupporting
confidence: 89%
“…Six studies provided an online or phone crisis management system ( Bauer et al, 2012 ; Ebert et al, 2013 ; Fichter et al, 2012 ; Gulec et al, 2014 ; Holländare et al, 2011 ; Kordy et al, 2016 ). Interventions differed regarding the sequence of intervention elements with consecutive ( Fichter et al, 2012 ; Holländare et al, 2011 ; Zwerenz et al, 2017b ) or flexible order ( Norlund et al, 2018 ; Willems et al, 2017a ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies ( n = 10) reported at least a medium follow-up period (6–12 months). Six studies reported a short (<6 months) ( Gulec et al, 2014 ; Kraft et al, 2017 ; Norlund et al, 2018 ; Schmädeke and Bischoff, 2015 ; Zwerenz et al, 2017b ; Zwerenz et al, 2017c ), and four studies a long-term follow-up period (>12 months) ( Fichter et al, 2013 ; Holländare et al, 2013 ; Jacobi et al, 2017 ; Kordy et al, 2016 ). Table 1 provides an overview of relevant characteristics of included studies ordered by the diagnostic focus of the studies (for a list of abbreviations of instruments, see Appendix D ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the latest research shows internet-based CBT (iCBT) may improve patient access to acceptable, effective, and cost-effective psychological treatment, 55 and has been found to reduce symptoms of depression and anxiety among patients with MI. 56 On the other hand, there are cultural differences in how patients address anxiety and depression, such as the forest therapy used among Koreans and Japanese, Taijiquan and Baduanjin exercises for Chinese, and religious beliefs of American and Indian, among others. 57 The limitations of this meta-analysis and our systematic review should be considered.…”
Section: Discussionmentioning
confidence: 99%